Locating critical prosumers in P2P dominant grids using state-sensitivity function - Pareek, Parikshit (2023)
This letter presents the idea of ranking critical prosumers in using a novel state-sensitivity function (SSF). The SSF is designed to work in a given nodal power injection hypercube, and thus the proposed ranking method captures the effect of injection subspace. An element-wise maximum Jacobian is obtained, that quantifies the worst-case sensitivity of each injection on each state. Results from various 33-Bus system configurations highlight the proposed method's capability in ranking state-injection risk pairs, providing node voltage risk levels and quantifying combined risk levels in peer-to-peer dominant grids.